Pengaruh Pemberian Ekstrak Rumput Laut Cokelat (Sargassum duplicatum) terhadap Peningkatan Kadar Hematokrit pada Darah Tikus Putih Jantan Galur Wistar (Rattus norvegicus) Anemia yang Diinduksi NaNO2 - Ayu Mayang; Liliawanti Liliawanti; Wachjudi Kurnia (Universitas Hang Tuah, 2020)
Anemia is still a high prevalence disease in Indonesia, caused by a lack of iron in the body. The components from brown seaweed such as cobalamin (vitamin B12), pyridoxine (vitamin B6), chlorophyll and iron (Fe) can increase red blood cells in the body. The purpose of this research was to determine the effect of brown seaweed (Sargassum duplicatum) which can increase hematocrit levels in the blood of white male wistar strain rat (Rattus norvegicus) suffered from anemia in induction NaNO2. This research uses an experimental laboratory method with a post test only control group design. The samples were 30 male rats divided into 3 treatment groups, the negative control group (K0) without treatment, the positive control (K1) be treated anemia given NaNO2 for 18 days without Sargassum duplicatum extract and treatment group (K2) treated with anemia given NaNO2 for 18 days without Sargassum duplicatum extract at a dose of 2,45gr / kgBB. On the 40th day, a blood sample was taken, then measured the hematocrit level.The results showed that the mean number of blood hematocrit levels in K2 was higher than K1, it showed a significant difference descriptively. Based on the KruskalWallis test, a value of 0.260 was obtained that p > 0,05 showed that there were no statistically significant differences between groups of experimental animals.From the results of this research, the conclusion is the administration of brown seaweed extract (Sargassum duplicatum) descriptively increased, but not statistically significant.